2001
DOI: 10.1002/etc.5620200820
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of sediment‐associated nitroaromatic and cyclonitramine compounds to benthic invertebrates

Abstract: The toxicity of nitroaromatic (2,4-diaminonitrotoluene [2,4-DANT] and 1,3,5-trinitrobenzene [TNB]) and 14C-labeled cyclonitramine compounds (hexahydro-1,3,5-trinitro-1,3,5-triazine [RDX] and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine [HMX]) to the marine polychaete Neanthes arenaceodentata and the estuarine amphipod Leptocheirus plumulosus following 10- or 28-d exposures to spiked sediments was investigated. Organismal-level effects on survival, growth, and reproduction and cellular-level effects on apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 36 publications
8
70
0
Order By: Relevance
“…Movement of TNT and related compounds from the sedimentporewater phase into the overlying water occurred during the static exposures in this study and has been reported previously (Lotufo et al, 2001;Rosen and Lotufo, 2005). Such movement of TNT has been attributed mostly to compound transfer from the porewater phase to the overlying water phase (Rosen and Lotufo, 2005).…”
Section: Tablesupporting
confidence: 78%
See 1 more Smart Citation
“…Movement of TNT and related compounds from the sedimentporewater phase into the overlying water occurred during the static exposures in this study and has been reported previously (Lotufo et al, 2001;Rosen and Lotufo, 2005). Such movement of TNT has been attributed mostly to compound transfer from the porewater phase to the overlying water phase (Rosen and Lotufo, 2005).…”
Section: Tablesupporting
confidence: 78%
“…A similar inverse relationship between spiking level and degree of transformation and disappearance has been previously observed for TNT and related compounds in sediments (Lotufo et al, 2001;Steevens et al, 2002;Conder et al, 2004;Lotufo and Farrar, 2005) and likely resulted from inhibition of microbial transformation as well as saturation of sites on the particles where covalent binding occurs.…”
Section: Tablesupporting
confidence: 73%
“…Extensive transformation of RDX occurred following spiking to fine-grained sediment (Lotufo et al 2001;Pennington et al 2011), but the transformation products were not identified. Different from the fate of RDX in organically-rich sediment, transformation was minimal in sandy sediment (Rosen and Lotufo 2005).…”
Section: Cyclic Nitramines Rdx Hmxmentioning
confidence: 99%
“…Metals absorption by these organisms is pertained to each individual metal concentration and chemical forms of metals transmission. Benthic organisms have been widely used in marine environmental monitoring, particularly in the toxicity of sediments, as they are directly affected by the pollutants in such sediments (Brown and Luoma 1995;Lotufo et al 2001;Zorita et al 2007).…”
Section: Introductionmentioning
confidence: 99%